Juridical Analysis of the Acquittal (Vrijspraak) Verdict for a TNI Soldier Committing the Crime of Adultery in the Military Judicial System (Case Study of Military Court Decision No. 10-K/PM II-08/AL/I/2023) - Oktavianus Deni (Goodwood Publishing, 2024)
Purpose: This study aims to examine the legal application in adultery cases involving TNI soldiers and analyze the indictment elements in Military Court Decision No. 10-K/PM II-08/AL/I/2023. Research Methodology: The research used is normative legal research or also called doctrinal legal research, namely research whose data sources are only secondary data. Results: The crime of adultery in the case of decision Number 10-K / PM II-08 / AL / I / 2023, that the processing of the case carried out by the military auditor on the case which was legally and convincingly proven was obtained through the examination report, the military auditor's demands regarding the proof of the elements of the indictment were declared unacceptable, because the military auditor in compiling the indictment used Article 281 point 1 of the Criminal Code alone, the indictment should have been compiled alternatively using Article 248 or 281 point 1 of the Criminal Code. So that in the application of the processing of the case there is an imbalance or inequality within the scope of the military auditor himself, with the author then making a legal comparison of the decisions that have permanent legal force that occurred in the military court environment.